2020
DOI: 10.1111/os.12756
|View full text |Cite
|
Sign up to set email alerts
|

High Hip Center Technique in Total Hip Arthroplasty for Crowe Type II–III Developmental Dysplasia: Results of Midterm Follow‐up

Abstract: Objectives We aimed to show the utility of high hip center technique used in patients with Crowe II–III developmental dysplasia of the hip at the midterm follow‐up and evaluated the clinical and radiographic results between different heights of hip center. Methods From December 2003 to November 2013, we retrospectively evaluated 69 patients (85 hips) with Crowe II–III dysplasia who underwent a high hip center cementless total hip arthroplasty. The patients were divided into two groups according to the height o… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
27
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 21 publications
(29 citation statements)
references
References 25 publications
1
27
0
1
Order By: Relevance
“…Although Nwankwo et al [ 11 ] and others found that the average rotational center rose 11 mm in their study, the rise in the average rotational center was only 7.5 mm in our study. These values represent excellent outcomes in numerous research reports regarding the placement of jumbo cups with high rotational centers in treating lateral acetabular defects[ 12 - 15 ]. Kelley[ 16 ]’s study of 23 jumbo cups placed with a high rotational center did not show loosening at an average of 35 mo of follow-up.…”
Section: Discussionmentioning
confidence: 82%
“…Although Nwankwo et al [ 11 ] and others found that the average rotational center rose 11 mm in their study, the rise in the average rotational center was only 7.5 mm in our study. These values represent excellent outcomes in numerous research reports regarding the placement of jumbo cups with high rotational centers in treating lateral acetabular defects[ 12 - 15 ]. Kelley[ 16 ]’s study of 23 jumbo cups placed with a high rotational center did not show loosening at an average of 35 mo of follow-up.…”
Section: Discussionmentioning
confidence: 82%
“…High hip center technique has become a prevalent method to address the problem of segmental deficiency in Crowe II–III DDH hips. The midterm results of this technique have been encouraging in recent reports [ 7 , 8 , 10 ]. However, for patients with bilateral dysplasia who have asymmetrical reconstruction of two hips, the outcomes are still unknown.…”
Section: Discussionmentioning
confidence: 99%
“…In a retrospective study of 85 HHC hips, Shen et al. [ 8 ] observed 12 acetabular cups with lateral placement greater than 10 mm compared with the anatomical center; however, no complications such as loosening and liner wear occurred with excessive lateralization. In this study, we also did not find any radiographic loosening or significant wear.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations